Pendekatan Lean Manufacturing Dengan Menggunakan Value Stream Mapping Untuk Mengeliminasi Pemborosan Pada Proses Produksi Celana Jeans - Narandana, Rifqi Fauzan; Aribowo, Budi (Universitas Mercu Buana, 2020)
Added value to a product becomes very important for the company or industry so that the product produced can compete with the competition. Providing added value to products can be done by designing more effective and efficient production processes. One way is to minimize and eliminate waste or waste in the production process. If this can be achieved, the company can meet the added value desired by consumers with minimal resources.The main purpose of the paper is to know how value stream mapping (VSM) is a powerful tool in lean implementation and to tackle the improvement areas from the current state & purpose the future state which helps in reducing the lead time, manufacturing cost and delivery in time without compromising for the quality of the product. VSM helps firms to understand and to improve continuously to work towards becoming lean enterprise. CV. X is a jeans convection company, this company has seven work stations found in the production section namely patterning, cutting, sewing, pairs of buttons, pairs of rivets, irons, packing, and shipping. The proposed recommendations for improvement are to carry out continuos flow at the work station of the button pairs up to the work station of packing and to change the delivery schedule of raw materials and to plan appropriate safety stock for CV.X. after the proposed recommendations for improvement, the final step is to draw future state mao and analyze the changes that occur so that the results obtained are reduced process lead time to 4.34, decrease in total inventory to 1345, decrease in total travel time to 25.3 and the last is Travel distance decreased to 3.9.